Limbah Kulit Aren Sebagai Adsorpsi Minyak Jelantah Dalam Pemberdayaan Organisasi PKK Desa Suka Makmur - Damanik, Melysa Andhieni; Marpaung, Arif Pratama; Sauna Putri, Shella; Ashri Safira, Dinda; Sadewo, M. Prasono (Lembaga Dongan Dosen, 2023)
The utilization of palm fruit leather waste as an adsorption of cooking oil to overcome the problem of the accumulation of palm fruit leather waste that occurs due to the disposal of palm fruit leather after the kolang kaling production process. The amount of kolang kaling fruit production that is not properly utilized by the local community can cause a buildup of waste that causes environmental pollution around the village of suka makmur. The method carried out starts with planning and preparation, namely discussing with partners related to the program and preparing all the materials needed in the activity. Furthermore, the implementation and assistance of activities, namely by carrying out activities in the period July - October. The results of this activity are the reduction of accumulated waste and adding new skills for pkk members in making floor cleaning soap using used cooking oil that has been adsorbed.